Irisin alleviated sepsis via enhancing macrophage phagocytosis and reducing inflammation levels - Gong, Zeen; Ji, Yunyan; Wu, Haiyang; Xue, Linli; Yu, Xiuju; Luo, Xiaomao; Yan, Yi; Lu, Jiayin; Wang, Juan; Dong, Yanjun; Wang, Haidong (Frontiers in Immunology, 2025)
BackgroundThe treatment of sepsis relies on antibiotics following infection; however, the emergence of resistant bacteria necessitates the development of new therapeutic agents. Irisin has been shown to alleviate symptoms in septic mice, although its mechanism of action remains unclear. Our aim was to determine the mechanism by which irisin alleviates sepsis.MethodsIn this study, septicemia was induced in mice using Escherichia coli CMCC 44102 (E) and Staphylococcus aureus CMCC 26003 (SA). The level of serum irisin were examined by ELISA kit. Mice with septicemia were intraperitoneally injected with irisin. The survival rate, body temperature, clinical manifestations, body’s bacterial load, the number of immune cells in blood, the level of inflammation in the body of the mice with septicemia were monitored to evaluate the effect of irisin therapy. The effect of irisin on the phagocytosis of spleen macrophages was observed by flow cytometry. LPS was used to induce inflammation in RAW264.7 cells and irisin was added to determine the effect of irisin on the level of macrophage inflammation.ResultsIn vivo, sepsis decreased serum irisin levels in mice. Irisin treatment in septicemic mice enhanced the phagocytosis of splenic macrophages, improved survival rates, accelerated body temperature recovery, alleviated clinical symptoms, reduced serum and organ inflammation, lowered bacterial loads in organs and body fluids. In vitro, irisin increased phagocytosis and reduced inflammation in RAW264.7 cells.ConclusionsIrisin improves splenic macrophage phagocytosis and reduces macrophage inflammation, thereby mitigating sepsis. Irisin holds potential as a therapeutic agent for sepsis treatment.